Diuretic Effects of Several Chemical and Herbal Compounds in Adult Laying Hens - Esfandiary, A.; Rajaian, H.; Asasi, K.; Lari, M. Ansari; Jalaei, J. (International Journal of Poultry Science, 2010)
Diuretic agents have been used in the treatment of several situations such as cardiopulmonary and urinary diseases in humans and animals, but they have not been extensively studied in poultry. Some Iranian poultry producers traditionally use urotropin (hexamine), alhagi (Camelorum fisch) and malt beverage to get therapeutic effect in broiler or laying hens. Diuretics may be used after drug therapy in order to get rid of tissue residues and in some toxicity conditions in birds. The purpose of this study was to evaluate the diuretic properties of several herbal and chemical agents in adult laying hens. Adult laying hens were randomly divided into 9 groups, each group consisting of 5 birds. Specific doses of diuretics were administrated to anesthetized hens (with xylazine and ketamine) following 24 h off-feed period. Urine samples were collected for 2 h after drug administration. Blood samples were also taken at 90 min. The concentrations of chloride, albumin, glucose, creatinine, uric acid and urea nitrogen were measured in serum and urine samples. Urine volume and specific gravity, sodium and potassium concentrations were also determined in urine. Statistical analysis of data showed that furosemide had a positive significant effect on urine volume compared to other agents. Urotropin also increased the urine volume but this effect was not significant. With respect to the effects on electrolytes (sodium, potassium and chloride), intramuscular furosemide, oral urotropin and hydrochlorothiazide exerted some changes, but no consistent pattern was observed with respect to the other factors measured in serum and/or in urine. Diuretic effect was more pronounced following intramuscular administration of furosemide.